2017
DOI: 10.1371/journal.pone.0174453
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors for compensated Advanced Chronic Liver Disease (c-ACLD) in patients with chronic Hepatitis Delta Virus (HDV) infection

Abstract: ObjectiveThe study aimed to evaluate the prevalence and predictor factors for compensated advanced chronic liver disease (c-ACLD) in patients with hepatitis Delta virus (HDV) infection.MethodsThis cross-sectional study included consecutive HDV-infected patients defined by positive anti-HDV. Patients with hepatitis C coinfection, liver transplantation or presence of conditions that limit liver (LSM) or spleen stiffness measurement (SSM) were excluded. Blood tests, abdominal ultrasound, SSM and LSM by transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This figure is a minimum since HDV could not be amplified and genotyped from several of these patients. These data reinforce the important role of HBV/HDV coinfection (especially by the HDV‐3 genotype) on the severity of liver disease …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This figure is a minimum since HDV could not be amplified and genotyped from several of these patients. These data reinforce the important role of HBV/HDV coinfection (especially by the HDV‐3 genotype) on the severity of liver disease …”
Section: Discussionsupporting
confidence: 73%
“…These data reinforce the important role of HBV/HDV coinfection (especially by the HDV-3 genotype) on the severity of liver disease. [4][5][6][7][8] It has been postulated that there is a specific interaction of HDV-3/HBV-F genotypes possibly associated with fulminant hepatitis in Amazonian populations. 4,10,13 However, our data show that the HDV-3 genotype could be associated with the more prevalent HBV strains in a given population.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Ministry of Health (MoH) of Brazil estimated that 1.4–1.7 million people are chronically infected with hepatitis C virus (HCV) [ 7 ]. Presence of advanced fibrosis was reported in up to 30% of patients with hepatitis B and Delta coinfection in western Amazon Basin [ 8 , 9 ] and more than 800,000 liver-related hospitalizations (~30,000 admissions per year) were performed in the last decade in Brazil [ 10 ]. We previously reported a nationwide analysis describing an increase in number of deaths due to liver diseases and cirrhosis in the last decade [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study by Couto et al gives some support to the use of Fibroscan in chronic HDV infection. Although it was not a validation study of Fibroscan vs biopsy, the authors reported a significant correlation between Fibroscan results and various measures of advancing liver fibrosis, such as splenic volume, bilirubin, platelet count, APRI and FIB‐4, in 77 HDV‐infected patients in Brazil …”
Section: Discussionmentioning
confidence: 99%
“…Of 1267 patients included in this study, 748 (59.0%) were men and the median age was 31 years (interquartile range [IQR] [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] by multiple logistic analysis, probably because of the small sample size available for the logistic model.…”
Section: Baseline Characteristicsmentioning
confidence: 99%